Youth drinking: the impact of socialisation agents and personal attitudes on alcohol consumption among the youth in South Africa - Matjila, Kagiso (My University, 2017)
The research investigated the impact of three socialisation agents (i.e. advertising, parents and peers) and personal attitudes on alcohol consumption among South Africa youth. There is a growing concern of the high and year-on-year increase in alcohol consumption in the country which has not only been linked to social ills such as crime, violence, sexual abuse, but also to health concerns. Of greater concern is the ever growing penetration of alcohol consumption among young people. The South African government has pledged its support to the World Health Organisation to reduce the harmful use of alcohol; and appointed an Inter-Ministerial Committee (IMC) to develop programs that seek to reduce alcohol-related harm. The findings generated from this study provide insights into social influences and social interventions that might assist in reducing the harmful use of alcohol. The research employed a quantitative approach and was cross-sectional in design. Non-random quota sampling was employed and a total of 300 youths from Gauteng were issued with self-administered questionnaires. The young people were at different life stages; students, blue and white collar workers. Using SPSS 22 and AMOS 22 software programs, structural equation modelling (SEM) was performed to analyse the data set. The results revealed that personal attitude, peer influence, and advertising exposure have positive and significant influences on youth alcohol consumption. Parental influence had a positive, yet weak and unimportant, effect on youth alcohol consumption. The implication of the results in this study is that government, alcohol manufacturers and the community at large need to consider, and possibly prioritise, other harmful uses of alcohol interventions and address personal attitudes that young people have developed to reduce the effects of peer pressure.
A research study submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing (MMSM) Wits Business School May 2017
Keywords: Youth--Alcohol use--South Africa; Adolescent psycholgy--South Africa; Peer pressure--South Africa